“We struggle with the earth everyday”: parents’ perspectives on the capabilities for healthy child growth in haor region of Bangladesh - Chakraborty, Barnali; Yousefzadeh, Sepideh; Darak, Shrinivas; Haisma, Hinke (Springer Link, 2022)
This article was published in BMC Public Health [ © The Author(s). 2020 Open Access This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/).] and the definite version is available at: https://doi.org/10.1186/s12889-020-8196-9 The Journal's website is at: https://link.springer.com/article/10.1186/s12889-020-8196-9